Republic of Mozambique : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Mozambique. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2019)
Mozambique's economic situation had been improving until Tropical Cyclone Idai and Kenneth hit the country in March and April, respectively. Economic growth was recovering gradually and becoming broader based, and inflation reached low single digits. Economic activity is expected to decelerate sharply in 2019 due to the supply shock to productive capacity, but it should rebound to pre-cyclone levels by 2020. In April, the IMF Executive Board approved USD 118 million in emergency assistance under the Rapid Credit Facility (RCF). The authorities are committed to macroeconomic stability while fostering inclusive growth and addressing governance challenges.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet